Seventeenth summer - Daly, Maureen, 1921-2006. (New York : Simon Pulse, 2010)
Seventeen-year-old Angie, living with her family in Fond du Lac, Wisconsin, finds herself in love for the first time the summer after high school graduation.
5-8.
English.
Keywords: Adolescence -- Juvenile fiction; Adolescence -- Fiction; Love -- Fiction; Adolescence -- Fiction; Love stories; Love stories